Humanitarian logistics management in the previus stages to the disaster: systematic review of the literature (2017)
The aim of this paper is to analyze how mitigation and preparedness stages that are part of the process of humanitarian logistics are presented in the literature related with the topic. For this, a systematic review of the literature was conducted using application Tree of Science of the Universidad Nacional de Colombia in Manizales. The review allows recognize the importance that these stages have on the level of disaster response, as well as the types of disasters and mitigation and preparation decisions most commonly addressed. Likewise, a smaller participation of these topics is evidenced in the specialized literature. Therefore, extend the study of the stages of mitigation and preparedness to other types of disasters and other geographical contexts is a field of interest for future research.